Long‐Term Follow‐Up on Systemic Bevacizumab Treatment in Recurrent Respiratory Papillomatosis. (31st December 2020) - Evers, Georg; Schliemann, Christoph; Beule, Achim; Schmidt, Lars‐Henning; Schulze, Arik B.; Kessler, Christina; Hoffmann, Thomas K.; Wiewrodt, Rainer; Groll, Andreas H.; Bleckmann, Annalen; Rudack, Claudia; Berdel, Wolfgang E.; et al.
Abstract : Objectives/Hypothesis: Recurrent respiratory papillomatosis (RRP) is a primarily benign disease affecting the entire respiratory tract. Treatment is challenging and usually involves surgical interventions and adjuvant medications. Previously, promising results on systemic administration of bevacizumab have been reported. However, experience on long‐term systemic use in patients with RRP is not yet available. Here, we present our long‐term follow‐up on RRP patients undergoing systemic bevacizumab treatment. Study Design: Case series. Methods: To describe experience on long‐term systemic bevacizumab administration, we performed the underlying investigation. Clinical, radiological, and bronchoscopy data were collected. Results: To date, a total of n = 5 patients has been treated with systemic bevacizumab at Muenster University Hospital. With a median follow‐up since first systemic bevacizumab administration of 95.5 months long‐term follow‐up is illustrated. Following bevacizumab treatment partial remission or very good partial remission were achieved in all patients. After papilloma recurrence/progression due to bevacizumab discontinuation, further response was documented in all patients in whom bevacizumab was started again. In one patient, bevacizumab was discontinued due to loss of efficacy. Lung cancer developed in one patient with pulmonary papillomatosis prior to bevacizumab administration whereas three patients suffered from malignant transformation during bevacizumab treatment. Systemic bevacizumab led to long‐term reduction in surgical interventions in all patients. Except from mild proteinuria and hypertension in two patients therapy was well tolerated. Conclusions: Systemic bevacizumab represents a promising long‐term treatment option for aggressive forms of papillomatosis. Rate of malignant transformation under bevacizumab treatment, optimal treatment schedule, and influence on survival should be further evaluated in clinical trials. Level of Evidence: 4 Laryngoscope, 131:E1926–E1933, 2021